Tinjauan tentang Persepsi Mahasiswa terhadap Pelayanan Sistem Informasi Akademik IAIN Purwokerto - Muslih Aris Handayani (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2017)
One of the hallmarks in modernization is the technological development in all fields. This development is also reach the university environment particularly in the field of academic services. Internet – based academic services are continuously improved to achieve maximum services. This IAIN Purwokerto SIA system study was conducted to get an overview of the academic services based on internet platform. Objective of this study is to get an illustration of student’s perceptions towards academic information system services at IAIN Purwokerto. This research is quantitative descriptive type of study. Population of this study is students at IAIN Purwokerto. Total sample are 48 and randomly selected. Questionnaires were distributed to all respondents who are assumed representing the population of IAIN Purwokerto students. Result shows that 64.6% of students percepting that online academic services is considered as a useful services, 35.4% very useful, and 0% stated that it is very useless. Only 2,1% of them stated that the quality of online academic services is not very good. 41.7% not good, 56.3% stated that it is a good services. 2.1% Student’s said that the accessibility of academic services is very difficult. 25% said that it is difficult, 70.8% stated that is easy, 2.1% stated that it is very easy one. 10.4% of the students stated that there are no need of additional feature on online academic services, 0% stated that it is extremely unnecessary, 60,4% necessary, and 29,2 others stated that it is very necessary. 2,1% of the these students said that they never encountered any problem on the internet system, 52,1% occasionally encountered problems, 16,7% quite problematic, 29,2% very often problematic. 0% said that this internet system is very unnecessary to be improved, 2,1% no need improvement, 31,3% system’s improvement is necessary, and 66,7% highly needs improvement.